Pengaruh Information Technology Relatedness dan Sistem Pengendalian Manajemen Terhadap Kinerja Perusahaan - Luthvan Putra; Henri Agustin (Universitas Negeri Padang, 2016)
This research is aimed to examine and find out empirical evidence of the information technology relatedness and management control systems on company performance. The data are collected using total sampling method.The analysis of this research employs multiple regression. The sample in this study are all banking branch office in the city of Padang by the number of samples analyzed a total of 18 samples of the 25 samples studied. Research disseminated through questionnaires. Result show that Information Technology Relatedness have not significant effect on company performance and management control systems have significant effect on company Performance.Keyword: information technology relatedness, management control system, company performance..